Direct Instruction and Teaching Games for Understanding in Volleyball Learning - Dian Fatimah Sobari; Tite Juliantine; Burhan Hambali (Journal of Physical Education Health and Sport, 2025)
This study aimed to compare the effectiveness of the Direct Instruction (DI) and Teaching Games for Understanding (TGFU) learning models in improving volleyball game performance among beginner-level extracurricular participants at State Junior High School 12 Bandung. A quasi-experimental method with a pretest-posttest nonequivalent group design was used. The sample taken in this study consisted of 10 students, each divided into two groups: DI (n=5) and TGFU (n=5). In this study, the Game Performance Assessment Instrument was used as the research instrument. Statistical hypotheses were tested using paired sample t-test and independent sample t-test. The results showed that both models significantly improved volleyball game performance (p < 0.05). However, the improvement in the DI group (mean pretest 41.12 to posttest 85.80) was significantly higher than in the TGFU group (mean pretest 41.00 to posttest 63.40). the independent sample t-test showed a significant difference between the two groups (p = 0.000). It was concluded that H0 is rejected and Ha is accepted, so the DI model is more effective in improving volleyball game performance among beginners with low basic technical skills, likely due to its structured, technique-focused approach. These findings provide practical implications for physical education teachers in selecting and sequencing learning models according to student foundational skill levels.